Aplikasi Pengelolaan Catering pada Rezky Catering Berbasis Web - Muhammad Subhan Redho’i (mijournal.org, 2026)
Rezky Catering is a catering service provider in Banjarmasin City serving food package orders for weddings, celebrations, and institutional events. Data processing of catering order transactions has traditionally relied on physical logbooks and manual paper invoices. Main problems encountered include risks of transaction data loss, delays in recording down payments (DP) and remaining balances, and slow monthly sales report generation. This research aims to design and develop a Web-Based Catering Management Application for Rezky Catering using the Waterfall software development methodology. Development tools include PHP, MySQL, XAMPP, as well as DFD and ERD modeling. Testing results indicate that the application successfully increases catering order transaction efficiency, accelerates DP payment tracking, and simplifies daily, monthly, and annual sales report preparation accurately.